2021
DOI: 10.2991/assehr.k.211215.038
|View full text |Cite
|
Sign up to set email alerts
|

Creative Accounting: A Short Literature Review

Abstract: In the professional literature, creative accounting is understood as legitimate, which means that it is not illegal to the extent that it does not violate the legislation of the country. Although it is a numbers game that can mislead internal or external users of financial statements, in some cases it can help protect a business from bankruptcy or other adverse conditions. This paper aims to represents creative accounting through various studies by authors dealing with the issue. The studies included in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Previous research has shown that creative accounting practices affect the financial reporting quality (Johl et al, 2013;Tassadaq & Malik, 2015;Blazek et al, 2020;Cooray, Gunarathne & Senaratne, 2020;. The goal of using accounting standards and ethics in financial reporting is to raise awareness inside the organization of the necessity to uphold moral principles that foster customer confidence in the company's services (Blazek et al, 2020;Lenka & Katarina, 2021). In essence, innovative accounting ethics procedures exist to assist external auditors in enhancing their effectiveness and precision in identifying fraudulent transactions (Johl et al, 2013;Aprilia, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that creative accounting practices affect the financial reporting quality (Johl et al, 2013;Tassadaq & Malik, 2015;Blazek et al, 2020;Cooray, Gunarathne & Senaratne, 2020;. The goal of using accounting standards and ethics in financial reporting is to raise awareness inside the organization of the necessity to uphold moral principles that foster customer confidence in the company's services (Blazek et al, 2020;Lenka & Katarina, 2021). In essence, innovative accounting ethics procedures exist to assist external auditors in enhancing their effectiveness and precision in identifying fraudulent transactions (Johl et al, 2013;Aprilia, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In essence, innovative accounting ethics procedures exist to assist external auditors in enhancing their effectiveness and precision in identifying fraudulent transactions (Johl et al, 2013;Aprilia, 2017). Lenka and Katarina (2021) stated that six principles that indicate the maximum use of creative accounting practices are flexibility in regulation, scarcity of regulations, assumptions about the future, use of artificial transactions, timing, reclassification, and presentation of financial number games. Due to their lack of accounting knowledge and inability to conduct indepth research, most stakeholders need help recognizing or comprehending the financial numbers game's truths (Bhasin, 2016b;Christian & Julyanti, 2021;Hrosova, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 99%